2000
DOI: 10.1590/s0074-02762000000500019
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an enzyme immunoassay for hepatitis C virus antibody detection using a recombinant protein derived from the core region of hepatitis C virus genome

Abstract: This study was undertaken to evaluate an enzyme immunoassay (EIA) for hepatitis C virus antibody detection (anti-HCV

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Lopes et al reported the evaluation of an EIA for anti-HCV antibody detection using single antigen [79]. A recombinant c22 antigen was localized on the solid-phase and allowed to complex with anti-HCV antibodies in serum samples to detect anti-HCV IgG.…”
Section: Enzyme Immunoassay (Eia)mentioning
confidence: 99%
“…Lopes et al reported the evaluation of an EIA for anti-HCV antibody detection using single antigen [79]. A recombinant c22 antigen was localized on the solid-phase and allowed to complex with anti-HCV antibodies in serum samples to detect anti-HCV IgG.…”
Section: Enzyme Immunoassay (Eia)mentioning
confidence: 99%
“…The diagnosis of anti‐HCV with third‐generation EIA offers high sensitivity and specificity, achieving a correct diagnosis in approximately 97% of the cases 13 . The detection of HCV‐RNA quantitative, which reflects the infection in course, is routinely performed using reverse transcriptase polymerase chain reaction (RT‐PCR) 14–17 . In clinical practise, blood samples are used to diagnose anti‐HCV and HCV‐RNA, which necessitates the puncture of a peripheral blood vein 18 .…”
Section: Introductionmentioning
confidence: 99%
“…13 The detection of HCV-RNA quantitative, which reflects the infection in course, is routinely performed using reverse transcriptase polymerase chain reaction (RT-PCR). [14][15][16][17] In clinical practise, blood samples are used to diagnose anti-HCV and HCV-RNA, which necessitates the puncture of a peripheral blood vein. 18 Furthermore, the longer the time for RT-PCR, the greater the risk of contamination, and the high cost of the procedure limits its use in daily practise.…”
mentioning
confidence: 99%
“…The study of anti‐HCV with third‐generation EIA offers high sensitivity and specificity, achieving a correct diagnosis in approximately 97% of cases. The detection of HCV‐RNA, which reflects the infection in course, is routinely performed using polymerase chain reaction (PCR) [9–12]. In practice, both the study of anti‐HCV and HCV‐RNA are carried out with blood samples, which requires the puncturing of a peripheral vein.…”
Section: Introductionmentioning
confidence: 99%